106k views
4 votes
Perform the indicated operation to write given polynomial in standard form: (x^2+ 7x − 12)(x^2 − 9x +1)

1 Answer

2 votes

Answer:

The expression in standard form will be
x^4=2x^3-50x^2+115x-12

Explanation:

We have given polynomial
(x^2+7x-12)(x^2-9x+1)

We have to write the given polynomial in standard form

For writing in standard form we have to first multiply then write in order

So after multiplication


(x^2+7x-12)(x^2-9x+1)=x^4-9x^3+x^2+7x^3-63x^2+7x-12x^2+108x-12=x^4=2x^3-50x^2+115x-12

So the expression in standard form will be
x^4=2x^3-50x^2+115x-12

User Nobel
by
5.1k points